Preparation method of near-infrared laser sensitive composite energetic material
Patent Information
- Application Number
- CN202411263730.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-09-10
AI Technical Summary
其中,所用炭材料包括炭黑、石墨、氧化/还原石墨烯、C纳米管等,以炭黑的激光增敏效果最好,可减少点火能量阈值、缩短点火延迟时间,但是炭黑易发生自身团聚而影响在药剂中的均匀分布,进而影响点火、传火的连续性;纳米金属包括Au、Ti、Ni、Cu、Mg、Al等,利用了金属纳米粒子良好的导电、导热、光学、表面自由电子等离子体共振效应等光学性质和光热转化性能,以非溶剂悬浮-重结晶法、研磨混合法、超声悬浮法等方法制备,掺杂于炸药晶体表面或晶体内部,适用的点火波长各有所不同,都能在一定程度上降低点火阈值和缩短延迟时间,但仍然存在掺杂不均、使炸药晶体出现裂纹、易氧化、或成本高昂不适合实际应用、与炸药晶体颗粒之间以静电吸附作用复合易发生迁移等问题
[0022](1)以硝酸银(AgNO3)和邻苯二胺(oPD)、奥克托今(HMX)为原料,银离子与邻苯二胺发生氧化还原反应生成纳米单质银与邻苯二胺低聚体,然后邻苯二胺低聚体进一步聚合生成聚邻苯二胺(PoPD),采用纳米银和光敏导电聚合物聚邻苯二胺协同增加近红外激光敏感性能;纳米银比纳米金价格便宜,比其它如Au、Ti、Ni、Cu、Mg、Al等纳米金属易制备;
Smart Images

Figure CN119118758B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of laser-sensitive composite energetic materials, specifically relating to a method for preparing a near-infrared laser-sensitive composite energetic material. Background Technology
[0002] Developing high-safety, high-energy, insensitive munitions is an urgent requirement and key need in the field of energetic materials. Laser ignition technology for energetic materials is one of the important ways to solve the safety problem of munitions. Laser ignition systems for energetic materials require the use of laser-sensitive, insensitive, high-energy explosives; therefore, research on laser ignition of high-energy-density nitramine explosives, represented by HMX and CL-20, has attracted attention. Laser ignition of energetic materials is based on the interaction between a laser of a certain wavelength and the energetic material, and its mechanism includes photochemical, photothermal, photoelectric, and photo-impact effects. Studies have shown that nitramine explosive crystals such as HMX and CL-20 have strong absorption in the ultraviolet band, but almost no absorption in the near-infrared band with wavelengths greater than 800 nm, making them difficult to ignite with near-infrared lasers. However, ultraviolet lasers are large, expensive, and unsuitable for laser ignition systems; small and inexpensive semiconductor diode lasers mostly operate in the near-infrared region with wavelengths greater than 800 nm. Therefore, it is necessary to improve the near-infrared laser sensitivity of nitramine explosive crystals such as HMX and CL-20, while reducing mechanical sensitivity, in order to achieve laser ignition and meet the requirements of laser ignition systems for energetic materials.
[0003] The main way to improve the near-infrared laser sensitivity of nitramine explosive crystals such as HMX and CL-20 is to add or dope photosensitive materials, including carbon materials, dyes, and nano-metals. The carbon materials used include carbon black, graphite, graphene oxide / reduced oxide, and C nanotubes. Carbon black has the best laser sensitization effect, which can reduce the ignition energy threshold and shorten the ignition delay time. However, carbon black is prone to self-agglomeration, which affects its uniform distribution in the explosive and thus affects the continuity of ignition and ignition transmission. Nanometals include Au, Ti, Ni, Cu, Mg, and Al. They utilize the good electrical conductivity, thermal conductivity, optical properties, surface free electron plasmon resonance effect, and photothermal conversion performance of metal nanoparticles. They are prepared by non-solvent suspension-recrystallization, grinding and mixing, and ultrasonic suspension methods. They are doped on the surface or inside the explosive crystals. The applicable ignition wavelengths vary. They can all reduce the ignition threshold and shorten the delay time to a certain extent, but there are still problems such as uneven doping, cracks in the explosive crystals, easy oxidation, high cost that is not suitable for practical applications, and easy migration between the explosive crystal particles due to electrostatic adsorption. However, while doping with nano-metals to increase the laser sensitivity of explosive crystals has advantages, further in-depth research is needed on preparation methods, composite mechanisms, laser ignition mechanisms, and comprehensive mechanical and thermal sensitivity performance to promote practical applications. Summary of the Invention
[0004] One object of the present invention is to solve at least the above-mentioned problems and / or defects, and to provide at least the advantages described below.
[0005] To achieve these objectives and other advantages according to the present invention, a method for preparing near-infrared laser-sensitive composite energetic materials is provided, comprising an additive process:
[0006] Step 1: First, recrystallize industrial octogen (HMX) to obtain recrystallized octogen (HMX). R Prepare o-phenylenediamine (oPD) crystals for later use. Dissolve o-phenylenediamine in ultrasonically deoxygenated deionized water at room temperature to obtain o-phenylenediamine solution I. Then, under stirring conditions, add HMX... R When the crystals are added to o-phenylenediamine solution I, a suspension system A is formed;
[0007] Step 2: Dissolve silver nitrate in deionized water that has been deoxygenated by ultrasound at room temperature to prepare silver nitrate solution I. Add silver nitrate solution I dropwise to system A at a certain rate. After the addition is complete, continue stirring to react.
[0008] Step 3: After the reaction is complete, perform vacuum filtration, wash the precipitate several times with deionized water, and then dry the filter cake in a vacuum drying oven to obtain the composite energetic material.
[0009] Preferably, steps one and two are adjusted to perform an inverse addition:
[0010] S1. First, industrial octogen (HMX) is recrystallized to obtain recrystallized octogen (HMX). R (Crystals, for later use) Silver nitrate solution II was prepared by dissolving silver nitrate in ultrasonically deoxygenated deionized water at room temperature. Then, under stirring conditions, HMX was added... R When the crystals are added to silver nitrate solution II, suspension system B is formed;
[0011] S2. Dissolve o-phenylenediamine in deionized water that has been deoxygenated by ultrasonication at room temperature to prepare o-phenylenediamine solution II. Add o-phenylenediamine solution II dropwise to system B at a certain rate. After the addition is complete, continue stirring the reaction.
[0012] S3. After the reaction is complete, the mixture is filtered and the precipitate is washed several times with an appropriate amount of deionized water. Then the filter cake is dried in a vacuum drying oven to obtain the composite energetic material.
[0013] Preferably, in step one, the concentration of the prepared o-phenylenediamine solution I is 0.0020–0.0300 g / mL, and the concentrations of o-phenylenediamine and HMX are... R The mass ratio of the crystals is 0.03 to 0.35:1, and the stirring time is 0.5 to 6 hours.
[0014] Preferably, in step two, the concentration of silver nitrate solution I is 0.002–0.008 g / mL, and the silver nitrate and HMX... R The mass ratio of the crystals was 0.03–0.15:1, and the silver nitrate solution was accelerated at a rate of 0.1–1.0 mL / min for stirring for 4–24 h.
[0015] Preferably, in step three, the drying temperature is 45–60°C and the drying time is 10–24 hours.
[0016] Preferably, in step S1, the concentration of the prepared silver nitrate solution II is 0.002–0.008 g / mL, and the silver nitrate and HMX... R The mass ratio of the crystals is 0.03 to 0.15:1.
[0017] Preferably, in S2, the concentration of o-phenylenediamine solution II is 0.0030–0.0300 g / mL, and o-phenylenediamine and HMX... R The mass ratio of the crystals was 0.03–0.35:1, the drop rate of the o-phenylenediamine solution II was 0.1–1.0 mL / min, and the reaction was stirred for 4–24 h.
[0018] Preferably, in step S3, the drying temperature is 45–60°C and the drying time is 10–24 hours.
[0019] Preferably, the positive addition method is improved by adding sodium chloride or sodium nitrate to the mixture after step two, with the amount added being HMX. R Add 0.1–1 wt% of the crystals and continue stirring for 2–6 hours.
[0020] Preferably, the reverse addition method is improved by adding sodium chloride or sodium nitrate to the mixture after step S2, with the amount added being HMX. R Add 0.1–1 wt% of the crystals and continue stirring for 2–6 hours.
[0021] The present invention has at least the following beneficial effects:
[0022] (1) Using silver nitrate (AgNO3), o-phenylenediamine (oPD), and octogen (HMX) as raw materials, silver ions undergo a redox reaction with o-phenylenediamine to generate nano-elemental silver and o-phenylenediamine oligomers. Then, the o-phenylenediamine oligomers are further polymerized to generate poly-o-phenylenediamine (PoPD). The near-infrared laser sensitivity is increased by synergistic use of nano-silver and photosensitive conductive polymer poly-o-phenylenediamine. Nano-silver is cheaper than nano-gold and easier to prepare than other nano-metals such as Au, Ti, Ni, Cu, Mg, and Al.
[0023] (2) At room temperature, in-situ growth technology was used to grow silver nanoparticles on recrystallized HMX in a solid-liquid system. R On the crystal surface, strong interfacial interactions make it difficult for nano-silver particles to detach from HMX. R Surface detachment;
[0024] (3) In this preparation system, nano-silver and poly(o-phenylenediamine) (PoPD) are grown in the same system, in HMX R Poly(o-phenylenediamine) adsorbed in HMX in / Ag / PoPD composite energetic materials R Particle surface or filling HMX R Between particles, photosensitivity is increased and mechanical sensitivity is reduced, thus improving the laser ignition performance of composite energetic materials;
[0025] (4) HMX was prepared in situ in a solid-liquid system at room temperature using an in-situ growth technique. R / Ag / PoPD composite photosensitive energetic material, by adding a small amount of sodium chloride or sodium nitrate to increase the electrolyte concentration in the system, thereby increasing the absorption of the product to near-infrared laser, thereby improving the near-infrared laser sensitivity and improving the laser ignition performance of the product. The reaction conditions are mild, easy to operate, safe and energy-saving.
[0026] (5) The technical solution adopted in this invention can be extended to the design and preparation of non-water-soluble energetic matrix photosensitive composite energetic materials such as RDX and CL-20, and can be improved in terms of the structure and type of photosensitive conductive polymer, such as adding hydroxyl groups to make it have a stronger adsorption force with the HMX crystal plane so that the two are more closely combined, or making it have stronger near-infrared absorption.
[0027] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached image description:
[0028] Figure 1 This is a flowchart of the positive addition method of the present invention;
[0029] Figure 2 This is a flowchart of the inverse addition method of the present invention;
[0030] Figure 3 HMX in Embodiment 1 of the present invention R SEM image before compositing;
[0031] Figure 4 Here is a SEM image of the composite energetic material obtained in Comparative Example 1 of this invention;
[0032] Figure 5 Here is a SEM image of the composite energetic material obtained in Example 2 of this invention;
[0033] Figure 6 Here is a SEM image of the composite energetic material obtained in Example 1 of this invention;
[0034] Figure 7 Here is a SEM image of the composite energetic material obtained in Example 3 of this invention;
[0035] Figure 8 Here is a SEM image of the composite energetic material obtained in Example 4 of this invention;
[0036] Figure 9 Here is a SEM image of the composite energetic material obtained in Example 5 of this invention;
[0037] Figure 10 Here is a SEM image of the composite energetic material obtained in Example 6 of this invention;
[0038] Figure 11 Here is a SEM image of the composite energetic material obtained in Example 7 of this invention;
[0039] Figure 12 Here is a SEM image of the composite energetic material obtained in Example 8 of this invention;
[0040] Figure 13 The images show the PXRD patterns of the composite energetic materials obtained in Examples 1, 3-5, and Comparative Example 1 before HMX composite formation in Example 1 of this invention.
[0041] Figure 14 The figures show the test results of the laser ignition performance of the composite energetic materials obtained in Examples 1, 3 to 5 of the present invention. Detailed implementation method:
[0042] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.
[0043] Example 1
[0044] A method for preparing near-infrared laser-sensitive composite energetic materials, in this embodiment using a direct additive method:
[0045] Step 1: First, recrystallize industrial octogen (HMX) to obtain recrystallized octogen (HMX). R Prepare the crystals. Add 10 mL of deionized water to a flask at room temperature, add a magnetic stir bar, and sonicate for 15 min to remove O2. Then add 0.0400 g of o-phenylenediamine (oPD) and sonicate for approximately 30 min to dissolve the oPD, obtaining oPD solution I. Add 0.9800 g of recrystallized octogen (HMX) to oPD solution I. R The SEM image is attached. Figure 3The suspension system A was obtained by magnetic stirring at room temperature for 2 hours.
[0046] Step 2: At room temperature, add 10 mL of deionized water to a beaker, add a magnetic stir bar, sonicate for 15 min to remove O2, then add 0.0315 g AgNO3 (of which the Ag content is 0.0200 g), dissolve, and obtain AgNO3 solution I; at 25 °C, add the prepared AgNO3 solution I dropwise to suspension system A at a rate of 0.5 mL / min. After complete addition, continue stirring and reacting for 8 h.
[0047] Step 3: After the reaction is complete, perform vacuum filtration, wash the precipitate several times with an appropriate amount of deionized water, and then dry the filter cake in a vacuum drying oven at 45°C for 24 hours to obtain HMX. R / Ag / PoPD composite energetic material, labeled as A-2%Ag.
[0048] Example 2
[0049] A method for preparing near-infrared laser-sensitive composite energetic materials, in this embodiment using the inverse addition method:
[0050] S1. First, industrial octogen (HMX) is recrystallized to obtain recrystallized octogen (HMX). R The crystals were prepared and set aside. At room temperature, 10 mL of deionized water was added to a 50 mL flask, a magnetic stir bar was added, and the mixture was sonicated for 15 min. Then, 0.0315 g of AgNO3 (containing 0.0200 g of Ag) was added and dissolved to obtain AgNO3 solution II. 0.9800 g of HMX was then added to this solution. R Stir magnetically at room temperature for 2 hours to obtain suspension system B;
[0051] S2. Take 10 mL of deionized water at room temperature and sonicate for 15 min. Add 0.0800 g of oPD and sonicate for 30 min to dissolve oPD, obtaining oPD solution II. Add oPD solution II dropwise to suspension system B at a rate of 0.5 mL / min. After complete addition, continue stirring and react for 8 h.
[0052] S3. After the reaction is complete, the mixture is filtered, and the precipitate is washed several times with an appropriate amount of deionized water. Then, the filter cake is dried in a vacuum drying oven at 45°C for 24 hours to obtain HMX. R / Ag / PoPD composite energetic material, labeled as B-2%Ag.
[0053] Example 3
[0054] The difference between this embodiment and Example 1 is that the amount of o-phenylenediamine (oPD) added is 0.1200g, and HMX... RThe amount added was 0.9700g, the amount of AgNO3 used was 0.0471g, and all other steps were the same as in Example 1, finally yielding HMX labeled A-3%Ag. R / Ag / PoPD composite energetic materials.
[0055] Example 4
[0056] The difference between this embodiment and Example 1 is that the amount of o-phenylenediamine (oPD) added is 0.1600g, and HMX... R The amount added was 0.9600g, the amount of AgNO3 was 0.0628g, and all other steps were the same as in Example 1, finally yielding HMX labeled A-4%Ag. R / Ag / PoPD composite energetic materials.
[0057] Example 5
[0058] The difference between this embodiment and Example 1 is that the amount of o-phenylenediamine (oPD) added is 0.2000g, and HMX... R The amount added was 0.9500g, the amount of AgNO3 used was 0.0785g, and all other steps were the same as in Example 1, finally yielding HMX labeled A-5%Ag. R / Ag / PoPD composite energetic materials.
[0059] Example 6
[0060] The difference between this embodiment and Embodiment 2 is that the amount of AgNO3 added is 0.0471g, and the amount of HMX is... R The amount added was 0.9700 g, the amount of o-phenylenediamine (oPD) was 0.1200 g, and all other steps were the same as in Example 2, finally yielding HMX labeled B-3%Ag. R / Ag / PoPD composite energetic materials.
[0061] Example 7
[0062] The difference between this embodiment and Embodiment 2 is that the amount of AgNO3 added is 0.0628g, and the amount of HMX is... R The amount added was 0.9600 g, the amount of o-phenylenediamine (oPD) was 0.1600 g, and all other steps were the same as in Example 2, finally yielding HMX labeled B-4%Ag. R / Ag / PoPD composite energetic materials.
[0063] Example 8
[0064] The difference between this embodiment and Embodiment 2 is that the amount of AgNO3 added is 0.0785g, and the amount of HMX is... RThe amount added was 0.9500g, the amount of o-phenylenediamine (oPD) was 0.2000g, and all other steps were the same as in Example 2, finally yielding HMX labeled B-5%Ag. R / Ag / PoPD composite energetic materials.
[0065] Example 9
[0066] The difference between this embodiment and embodiment 5 is that, after step two, 0.0050g of sodium chloride is added to the mixture, and the reaction is continued to be stirred for 4 hours.
[0067] The remaining steps are the same as in Example 5.
[0068] Example 10
[0069] The difference between this embodiment and embodiment 8 is that 0.0050g of sodium chloride is added to the mixture after step two, and the reaction is continued to be stirred for 4 hours.
[0070] The remaining steps are the same as in Example 8.
[0071] Comparative Example 1
[0072] A method for preparing near-infrared laser-sensitive composite energetic materials, in this embodiment using a direct additive method:
[0073] Step 1: First, recrystallize industrial octogen (HMX) to obtain recrystallized octogen (HMX). R Prepare the crystals. Add 10 mL of deionized water to a flask at room temperature, add a magnetic stir bar, and sonicate for 15 min to remove O2. Then add 0.0400 g of o-phenylenediamine (oPD) and sonicate for approximately 30 min to dissolve the oPD, obtaining oPD solution I. Add 0.9900 g of recrystallized octogen (HMX) to oPD solution I. R The SEM image is attached. Figure 3 The suspension system A was obtained by magnetic stirring at room temperature for 2 hours.
[0074] Step 2: At room temperature, add 10 mL of deionized water to a beaker, add a magnetic stir bar, sonicate for 15 min to remove O2, then add 0.0157 g AgNO3 (of which the Ag content is 0.0100 g), dissolve, and obtain AgNO3 solution I; at 25 °C, add the prepared AgNO3 solution I dropwise to suspension system A at a rate of 0.5 mL / min. After complete addition, continue stirring and reacting for 8 h.
[0075] Step 3: After the reaction is complete, perform vacuum filtration, wash the precipitate several times with an appropriate amount of deionized water, and then dry the filter cake in a vacuum drying oven at 45°C for 24 hours to obtain HMX. R / Ag / PoPD composite energetic material, labeled as A-1%Ag.
[0076] Comparative Example 2
[0077] Step 1: Add 10 mL of deionized water to a flask at room temperature, add a magnetic stir bar, sonicate for 15 min to remove O2, then add 0.0400 g of o-phenylenediamine (oPD), sonicate for about 30 min to dissolve oPD, and obtain oPD solution I; add 0.9900 g of industrial octogen (HMX) to oPD solution I, and stir magnetically at room temperature for 2 h to obtain suspension system A;
[0078] Step 2: At room temperature, add 10 mL of deionized water to a beaker, add a magnetic stir bar, sonicate for 15 min to remove O2, then add 0.0315 g AgNO3 (of which the Ag content is 0.0200 g), dissolve, and obtain AgNO3 solution I; at 25 °C, add the prepared AgNO3 solution I dropwise to suspension system A at a rate of 0.5 mL / min. After complete addition, continue stirring and reacting for 8 h.
[0079] Step 3: After the reaction is complete, perform vacuum filtration, wash the precipitate several times with an appropriate amount of deionized water, and then dry the filter cake in a vacuum drying oven at 45°C for 24 hours to obtain the HMX / Ag / PoPD composite energetic material.
[0080] Comparative Example 3
[0081] The only difference from Example 1 is that the deionized water containing dissolved oPD and AgNO3 was not subjected to ultrasonic oxygen removal. The resulting product was silver-gray and contained no PoPD.
[0082] Comparative Example 4
[0083] The only difference from Example 1 was that AgNO3 solution I was added dropwise to suspension A at a rate of approximately 2.0 mL / min. The generated elemental silver mainly accumulated on the reaction flask wall in the form of a silver mirror. The product obtained was a brownish-yellow HMX. R / PoPD composite energetic materials.
[0084] The composite energetic materials prepared in Examples 1-10 and Comparative Examples 1-4 were characterized in terms of morphology and structure, and their mechanical sensitivity and laser ignition performance were tested. Laser ignition tests were performed on the composite energetic materials with different Ag contents using a laser and high-speed photography. Ignition conditions: room temperature, normal pressure, open environment, laser wavelength 1064nm, pulse width 110μs, pulse repetition frequency 10Hz, spot diameter approximately 2mm, total laser path 175mm, and lens focal length 200mm.
[0085] The impact sensitivity and friction sensitivity of the prepared composite energetic material were tested according to methods 601.1 Impact Sensitivity (Explosion Probability Method) and 601.2 Friction Sensitivity (Explosion Probability Method) in GJB 772A—97 "Test Methods for Explosives". The mechanical sensitivity test results are shown in Table 1.
[0086] Table 1 HMX R Mechanical sensitivity test results of composite energetic materials with different Ag contents
[0087]
[0088] As can be seen from Table 1, HMX with different silver contents R The impact sensitivity of the / Ag / PoPD composite energetic material is below 20%, and the friction sensitivity gradually decreases with increasing silver content. For example, in Example 4, when the Ag content is 4%, the friction sensitivity of the composite energetic material drops to 48%, compared to the specific gravity-crystallized HMX. R The friction sensitivity is reduced by 40%. Compared to HMX crystals, the HMX prepared by the method of this invention... R / Ag / PoPD composite energetic materials can significantly improve mechanical sensitivity properties. Compared with direct addition, inverse addition generally results in lower impact sensitivity and friction sensitivity, indicating that inverse addition can better improve HMX. R The mechanical sensitivity of the / Ag / PoPD composite energetic material was compared. Comparative Example 1, due to its low silver content, still exhibited high friction sensitivity. Comparative Example 2, using unrecrystallized HMX crystals to prepare the composite energetic material, also showed high impact sensitivity. Comparative Example 3, failing to ultrasonically remove oxygen from the deionized water used to dissolve oPD and AgNO3, prevented oPD from polymerizing into PoPD, resulting in high friction sensitivity. Comparative Example 4, where elemental silver mainly accumulated as a silver mirror on the reaction vessel wall without growing within the energetic material, also exhibited high friction sensitivity.
[0089] from Figures 6-9 It can be seen that in the composite energetic material samples prepared by the additive method, the gem-like HMX R Nano-silver particles and linear PoPDs are distributed on the crystal surface. As the silver content increases, the number of nano-particles on the crystal surface increases, and some PoPDs are scattered in the HMX. R Between crystal grains. From Figure 5 , Figures 10-12 It can be seen that, with Figures 6-9 Similarly, in the composite energetic material samples prepared by the inverse addition method, the gem-like HMX R Nano-silver particles and linear PoPDs are distributed on the crystal surface. As the silver content increases, the number of nano-particles on the crystal surface increases, and some PoPDs are scattered in the HMX. RBetween crystal grains, compared to the product from the direct addition process, the HMX content in the inverse addition process sample is higher. R Slightly more PoPD lines are attached to the crystal surface, which can better improve HMX. R The mechanical sensitivity of the / Ag / PoPD composite energetic material is improved by the good ductility and thermal conductivity of the silver nanoparticles and the flexibility of the polymer PoPD. Their respective photoelectric and photothermal properties play a decisive role in improving the photosensitivity of the composite energetic material.
[0090] from Figure 13 It can be seen that the main diffraction peaks in the PXRD spectra of composite energetic materials with different silver contents are similar to those in the HMX spectrum. R The presence of minute diffraction peaks at the same positions as those in the standard cards Ag (PDF#87-0597) and PoPD (PDF#31-1837) indicates that the HMX crystal form in composite energetic materials with different silver contents is consistent with that of HMX. R Consistent with the presence of Ag and PoPD in the composite energetic material, this demonstrates the successful preparation of the composite energetic material and its maintenance of stable HMX. R Crystal form.
[0091] from Figure 14 It can be seen that, taking the laser ignition of samples with A-2% to A-5% silver content as an example, composite energetic materials with silver content of 2% to 5% can achieve good ignition under the same 1064nm laser energy. However, the composite energetic material with silver content of 1% in Comparative Example 1 cannot achieve good self-sustaining combustion and is not listed here. Furthermore, with the increase of silver content, the brightness and volume of the strongest single flame increase, indicating that with the increase of silver content and PoPD content, the utilization rate of laser energy by the composite energetic material increases, and the number of hot spots generated per unit time increases, effectively promoting ignition and combustion. In Examples 9 and 10, the addition of a small amount of sodium chloride to increase the electrolyte concentration in the system promotes the further polymerization of o-phenylenediamine oligomers in the solution to poly-o-phenylenediamine in the later stage of the reaction. This, to a certain extent, increases the content and degree of polymerization of PoPD in the product, improves the utilization rate of the raw material oPD, increases the absorption of the product to near-infrared laser, thereby improving the near-infrared laser sensitivity and improving the laser ignition performance of the product.
[0092] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. A method for preparing a near-infrared laser-sensitive composite energetic material, characterized in that, Including positive addition: Step 1: First, recrystallize the industrial octogen to obtain recrystallized octogen crystals for later use. Then, dissolve o-phenylenediamine in deionized water that has been deoxygenated by ultrasound at room temperature to prepare o-phenylenediamine solution I. Then, under stirring conditions, add the recrystallized octogen crystals to o-phenylenediamine solution I to form suspension system A. Step 2: Dissolve silver nitrate in deionized water that has been deoxygenated by ultrasound at room temperature to prepare silver nitrate solution I. Add silver nitrate solution I dropwise to system A at a certain rate. After the addition is complete, continue stirring to react. Step 3: After the reaction is complete, perform vacuum filtration, wash the precipitate several times with deionized water, and then dry the filter cake in a vacuum drying oven to obtain the composite energetic material.
2. The method for preparing near-infrared laser-sensitive composite energetic materials according to claim 1, characterized in that, Adjust steps one and two to make it an inverse addition: S1. First, recrystallize industrial octogen to obtain recrystallized octogen crystals for later use. Dissolve silver nitrate in deionized water that has been ultrasonically deoxygenated at room temperature to prepare silver nitrate solution II. Then, under stirring conditions, add the recrystallized octogen crystals to silver nitrate solution II to form suspension system B. S2. Dissolve o-phenylenediamine in deionized water that has been deoxygenated by ultrasonication at room temperature to prepare o-phenylenediamine solution II. Add o-phenylenediamine solution II dropwise to system B at a certain rate. After the addition is complete, continue stirring the reaction. S3. After the reaction is complete, the mixture is filtered and the precipitate is washed several times with an appropriate amount of deionized water. Then the filter cake is dried in a vacuum drying oven to obtain the composite energetic material.
3. The method for preparing near-infrared laser-sensitive composite energetic materials according to claim 1, characterized in that, In step one, the concentration of the prepared o-phenylenediamine solution I is 0.0020–0.0300 g / mL, the mass ratio of o-phenylenediamine to recrystallized octogen crystals is 0.03–0.35:1, and the stirring time is 0.5–6 h.
4. The method for preparing near-infrared laser-sensitive composite energetic materials according to claim 1, characterized in that, In step two, the concentration of silver nitrate solution I is 0.002–0.008 g / mL, the mass ratio of silver nitrate to recrystallized octogen crystals is 0.03–0.15:1, the dropping rate of silver nitrate solution I is 0.1–1.0 mL / min, and the reaction is stirred for 4–24 h.
5. The method for preparing near-infrared laser-sensitive composite energetic materials according to claim 1, characterized in that, In step three, the drying temperature is 45–60°C and the drying time is 10–24 hours.
6. The method for preparing near-infrared laser-sensitive composite energetic materials according to claim 2, characterized in that, In S1, the concentration of the prepared silver nitrate solution II is 0.002–0.008 g / mL, and the mass ratio of silver nitrate to recrystallized octogen crystals is 0.03–0.15:
1.
7. The method for preparing near-infrared laser-sensitive composite energetic materials according to claim 2, characterized in that, In S2, the concentration of o-phenylenediamine solution II is 0.0020–0.0300 g / mL, the mass ratio of o-phenylenediamine to recrystallized octogen crystals is 0.03–0.35:1, the dropping rate of o-phenylenediamine solution II is 0.1–1.0 mL / min, and the reaction is stirred for 4–24 h.
8. The method for preparing near-infrared laser-sensitive composite energetic materials according to claim 2, characterized in that, In step S3, the drying temperature is 45–60°C and the drying time is 10–24 hours.
9. The method for preparing near-infrared laser-sensitive composite energetic materials according to claim 1, characterized in that, The method for improving the positive addition method is as follows: after step two, sodium chloride or sodium nitrate is added to the mixture in an amount of HMX. R Add 0.1–1 wt% of the crystals and continue stirring for 2–6 hours.
10. The method for preparing near-infrared laser-sensitive composite energetic materials according to claim 2, characterized in that, The reverse addition method is improved by adding sodium chloride or sodium nitrate to the mixture after step S2, with the amount added being HMX. R Add 0.1–1 wt% of the crystals and continue stirring for 2–6 hours.
Citation Information
Patent Citations
Silver@polyaniline nano composite for photothermal therapy and preparation method thereof
CN106362150A
Preparation method of laser induced mono-disperse Ag-Ag2S nano-particle photocatalyst
CN106475038A